The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1017/s1463423620000055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidity on health-related quality of life among type 2 diabetic patients in primary care

Abstract: Background: Health-related quality of life (HRQL) is an important outcome for chronic diseases such as diabetes mellitus that is associated with complications, comorbidities, and lifelong care. Objectives: The present study aims to explore the impact of comorbidities on the different dimensions of HRQL among type 2 diabetic patients attending primary care. Methods: A total of 912 type 2 diabetic patients attending primary care centers in India were assessed using a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
3
25
0
3
Order By: Relevance
“…Further, this current study revealed that a higher number of chronic diseases was associated with a reduction in scores in all eight dimensions of the SF-36. Similar ndings have been highlighted elsewhere that studied the association between comorbid diseases and HRQoL [37][38][39].…”
Section: Discussionsupporting
confidence: 88%
“…Further, this current study revealed that a higher number of chronic diseases was associated with a reduction in scores in all eight dimensions of the SF-36. Similar ndings have been highlighted elsewhere that studied the association between comorbid diseases and HRQoL [37][38][39].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies in Odisha found that one-third of patients attending primary care settings had multiple chronic conditions (two or more) 28 29 30 31 . Similar findings have been observed in a chart review of the morbidity profile of urban primary care patients 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The ndings highlighted that age, ethnicity, and place of residence were found to be signi cantly associated with the being in one of the multimorbid groups. The ndings suggest that with increasing age [ (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) increased the risk of being in the "Hypertension-Diabetes-Arthritis' group compared to 'low-co morbidity' group. Whereas, residing in urban areas [AOR=0.72 (0.53, 0.98)] reduced the risk of being in the "Hypertension-Diabetes-Arthritis' group by compared to 'low co morbidity' group.…”
Section: Resultsmentioning
confidence: 99%
“…Multimorbidity thus requires a multifaceted approach which can be well integrated and approached with ease. [39,40,41,42] Strengths and limitations: Most of studies on multimorbidity in India are from the older population, anticipating the growing prevalence of multimorbidity among working age group studying the prevalence, patterns, and its health impact in working age population are pivotal. Also, to the best of our knowledge this is rst study from India, to identify the pattern of diseases using latent class analysis among working class group as most of the studies usually report most common dyad and triads.…”
Section: Discussionmentioning
confidence: 99%